Diseño, Material Didáctico Vegetal Estructurado y su influencia en el aprendizaje de biología para educación secundaria - Dávila Luliquis, Celia Noemí (2001)
The present experimental investigation was carried out with the educandos of the fourth degree of secondary education of the Agroindustrial National School with Technical Areas "Manuel Fidencio Hidalgo Flores" belongi.ng to the one to city of New Cajamarca, region San Martin. The problem, hypothesis, general and specific objective is had systematize by means of the relationship of the variables design, material didactic Structured Vegetable and the learning of Biology. The theoretical context of the design. material didactic Structured Vegetable was systematized endowing him of a purpose, of an action :field, of phases and diverse operations, so much in the preparation phase and application in the process of teaching- to learn and of a theoretical support based on the foundation of the biology of the learning the didactics, the chemistry the physics, and the: psychology. The presumption of the investigation hypothesis was the influence in the emanated learning of Biology of the design material didactic Structured Vegetable. Twenty-three educandos conformed the sample, fifteen of the experimental group and eight of the group control. The gathering of data was made, by means of pre and post trest. For the hypothesis test the statistical parameter T -Student was used. The sample was chosen aleatorily for the educandos assignment to the experimental group and control. In the first group they conformed it 15 educandos and in the second 8 educandos, obtaining a size of representative and appropriate sample of 23 educandos. In consequence, the conclusions reveal that the design, material didactic Structured Vegetable, stimulates the cerebral nervous cells of the right hemisphere, activating the prosecution of the practical experiences by means of the visualization manipulation and movements of concrete objects, cooperating with it to the learning cognitivo reflected in memorísticos, understanding, of application, of synthesis and of evaluation; to the affective learning reflected in the stimulation of attitudes toward the biology and the psychomotor learning.